The ratification of European Social Charter is important for the security of social rights in Lithuania - Žiūkas, Vytautas Povilas (Socialinė teorija, empirija, politika ir praktika, 2003)
The European Social Charter, the regulative area of the Charter, international liabilities of Lithuania after the ratification of the Charter and the effects of ratification to different social groups of Lithuania are discussed in the paper. The author describes the establishment and development of the Charter in the first part of the paper. The structure of the Charter is presented in the second part. The rights and obligations are presented in the third part.
Keywords: European Social Charter; Lithuania